Purification of a protein-based α-glucosidase inhibitor from Aspergillus niger VTCC 031 - Tran, Thanh Tuan; Nguyen, Nhat Linh; Nguyen, Thi Trung; Dao, Thi Mai Anh; Pham, Duy Nam; Luu, Minh Duc; Do, Thi Tuyen (Vietnam Journal of Biotechnology, 2026)
Alpha-glucosidase inhibitors, such as acarbose, voglibose, and miglitol, constitute a prevalent class of pharmaceuticals employed in the clinical management of diabetes. These inhibitors originate mostly from microorganisms, including Aspergillus sp., Bacillus sp., and Actinoplanes sp., representing a promising natural resource for identifying α-glucosidase inhibitors (AGIs) that offer enhanced therapeutic efficacy with reduced adverse effects. Aspergillus sp. is a fungus that has a rich array of secondary metabolites and produces several AGIs. In this work, the A. niger VTCC 031 demonstrated the capacity to manufacture compounds with significant α-glucosidase inhibitory activity, achieving a rate of 67.24%. The aqueous phase, obtained after ethyl acetate extraction, was purified using a Sephadex G100 column followed by a 30 kDa cut-off column, resulting in the purification of the α-glucosidase inhibitor characterized by low molecular weight protein properties. The SDS-PAGE chromatogram indicates that the active ingredient had a molecular weight of 14 kDa, with α-glucosidase inhibitory activity of 80.2% and a recovery efficiency of 0.02%. This study provides the scientific foundation for ongoing research into optimal conditions for the extraction and purification of the α-glucosidase inhibitor derived from the A. niger strain, a metabolically active fungus found in Vietnam.